Management of Educational Facilities and Infrastructure in the Department of Visual Communication Design - Putri Putri; Sirajuddin Saleh; Risma Niswaty; A. Hadijah Sulfiyani (Journal of Educational Development and Learning (JEDAL), 2025)
The management of educational facilities and infrastructure is very important in supporting effective learning, especially in the field of Visual Communication Design (DKV). This major requires facilities such as high-spec computers, up-to-date design software, creative classrooms, and other supporting infrastructure. The availability and management of these facilities plays a role in improving the quality of students' education and their ability to compete in the technology-based world of work. SMKN 1 Bambalamutu Pasangkayu Regency as a vocational school is responsible for preparing competent graduates. However, various challenges such as budget limitations, lack of maintenance, and non-conformity of facilities can hinder the achievement of maximum learning goals in the DKV department. The novelty of this research is its focus on a comprehensive analysis of the management process, from planning, procurement, use, to maintenance, as well as how these aspects support the quality of vocational education. This study aims to determine the management of educational facilities and infrastructure and identify supporting and inhibiting factors in the management. This study uses a qualitative approach with a descriptive type of research. Data was collected through observation, in-depth interviews, and documentation, then analyzed using data reduction techniques, descriptive data presentation, and conclusion drawn. The results of the study show that the management of facilities and infrastructure in the Department of Visual Communication Design is relatively good. Four indicators in management include: (1) systematic planning involving various parties; (2) procurement in accordance with procedures taking into account budget and priority needs; (3) the use of facilities that are not optimal due to certain limitations; and (4) maintenance that is carried out regularly and reactively. In conclusion, the management of facilities and infrastructure in the Department of Visual Communication Design is good, but it needs to be improved in optimizing the use of facilities, improving procurement procedures, and fulfilling learning needs in a more planned manner.